Influence of socio-ecological relationships on the risk of rain flooding in the urban area of Puquio district, Lucanas province, Ayacucho, Peru - Licla Tomayro, Luis Ricardo (2022)
The objective of this study is to determine the influence of socio-ecological relationships on the risk of pluvial flooding in the urban area of Puquio district. For this, the socio-ecological characterization of the local system was first carried out, which includes the identification and assessment of its relationships, then the risk of pluvial flooding was calculated through the hierarchical analysis process (Saaty, 1980), and finally, Spearman's correlation coefficient was used to analyze the correlation between the variables. The results establish that there is a moderate negative correlation of -0.554 between the variables, which indicates that in the areas of greatest economic growth and social development, neighborhoods of Ccayao and Pichccachuri, a moderate level of risk predominates, while in the areas of less development, neighborhoods of Chaupi and Ccollana, a high risk level predominates.